Electron impact mass spectrometry of some thienopyrimidone derivatives. Issue 1 (1998) - de Oliveira de Oliveira, Renata C. Renata C.; Freitas Freitas, Antonio C. C. Antonio C. C.; de Lima de Lima, José G. José G.
Abstract : The electron impact mass spectra of some previously synthesized thienopyrimidones have been recorded and the identity of various ions in the mass spectra established.